Identification of molecular subtypes and a prognostic signature based on chromatin regulators related genes in prostate cancer - Ma, Hangbin; Zhou, Cheng; Ge, Jianchao; Yu, Wandong; Zhou, Yinghao; Wang, Pengyu; Zhang, Xuehu; Zhang, Jun; Shi, Guowei (Frontiers in Genetics, 2023)
Prostate cancer (PCa) displays high heterogeneity of clinical and molecular phenotypes varying from indolent to metastatic disease. In this study, we aimed to construct a subtype for PCa and a gene signature to predict the recurrence-free survival (RFS) of PCa patient based on the chromatin regulators genes (CRGs). Strikingly, we identified two heterogeneous subtypes with distinct clinical and molecular characteristics. Furthermore, by performing differential analysis between the two CRGs subtypes, we successfully build a gene signature to predict the prognosis of PCa. Importantly, four genes including MXD3, SSTR1, AMH and PPFIA2 were involved in the signature and utilized to classify PCa patients into two risk groups. The high-risk group is characterized by the poor prognosis and more aggressive clinical features. Mover, we investigated the immune profile, landscape of mutation status and molecular pathway between the different groups. Additionally, drug-susceptibility testing was performed to explore sensitive drugs for the high-risk patient. Moreover, we found that MXD3 downregulation suppressed the proliferation of PCa cell lines in vitro. Altogether, our results highlight the signature based on CRGs as a powerful tool for predicting RFS of PCa as well as an indicator for personalized treatment of PCa patient.